The impact of neighbourhood environments on quality of life of elderly people: Evidence from Nanjing, China. (July 2018) - Feng, Jianxi; Tang, Shuangshuang; Chuai, Xiaowei
The connections between the built environment and quality of life are major concerns in the fields of geography and urban planning. Given that some developing countries, such as China, have a rapidly aging society, elderly people have become a social group that attracts growing interest among scholars and policy makers. However, the relationship between neighbourhood environments and the quality of life of the elderly has scarcely been referenced in previous literature. Based on a recent survey in Nanjing, China, this article investigates such connections through structural equations models. It notes that population density exerts an insignificant influence on the life satisfaction of the elderly, whereas built year has the largest impact, indicating the importance of interior environment to subjective wellbeing for the elderly in China. The other built environment factors (informal space and danwei ) that have Chinese features are negatively related to the quality of life of older people. Among life domains, the effects of health conditions, residential environments and transportation are stronger than those of social interaction, meaning that the elderly in China place greater emphasis on their basic needs than on higher life needs. This article has some policy implications for policy makers, including on urban form, informal spaces and style of residential communities. Relevant policies need to be carried out to promote the life satisfaction of elderly people in urban China.